2021
DOI: 10.1002/jclp.23232
|View full text |Cite
|
Sign up to set email alerts
|

Religious/spiritual struggles and psychological distress: A test of three models in a longitudinal study of adults with chronic health conditions

Abstract: Objective This study tested three conceptual explanatory models that have been theorized to account for the linkages between religious/spiritual (R/S) struggles and psychological distress: the primary model (i.e., R/S struggles lead to psychological distress), the secondary model (i.e., psychological distress leads to R/S struggles), and the complex model (i.e., R/S struggles and psychological distress reciprocally exacerbate each other). Methods Using prospective data from a sample of US adults living with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 57 publications
1
17
0
1
Order By: Relevance
“…Over the past several decades, hundreds of studies have shown that r/s struggles are widespread and have links to mental and physical health (see Pargament & Exline, 2021, 2022, for recent reviews). For example, results from a nationally representative sample in the U.S. (Abu-Raiya et al, 2015) showed many associations between r/s struggles and indicators of emotional distress, and longitudinal studies have clarified that r/s struggles can predict increases in distress over time (e.g., Cowden et al, 2022; see Bockrath et al, 2021, for a review). Other studies have shown links with faster disease progression among HIV patients (Ironson et al, 2011), greater odds of future hospitalizations among patients with heart failure (Park et al, 2011), higher mortality rates among hospitalized older adults (Pargament et al, 2001), and suicidality among veterans (Currier et al, 2020; Raines et al, 2017).…”
Section: Religious and Spiritual Strugglesmentioning
confidence: 99%
“…Over the past several decades, hundreds of studies have shown that r/s struggles are widespread and have links to mental and physical health (see Pargament & Exline, 2021, 2022, for recent reviews). For example, results from a nationally representative sample in the U.S. (Abu-Raiya et al, 2015) showed many associations between r/s struggles and indicators of emotional distress, and longitudinal studies have clarified that r/s struggles can predict increases in distress over time (e.g., Cowden et al, 2022; see Bockrath et al, 2021, for a review). Other studies have shown links with faster disease progression among HIV patients (Ironson et al, 2011), greater odds of future hospitalizations among patients with heart failure (Park et al, 2011), higher mortality rates among hospitalized older adults (Pargament et al, 2001), and suicidality among veterans (Currier et al, 2020; Raines et al, 2017).…”
Section: Religious and Spiritual Strugglesmentioning
confidence: 99%
“…This idea is related to the negative association that certain R/S variables have with physical health, mentioned above. Likewise, much research has been devoted to analyzing the relationships between variables of this type, such as R/S struggles [ 81 , 82 ] or mistrust in God [ 83 ] in relation to mental health. Therefore, we consider it necessary to further explore the effect on the physical health of oncology patients of R/S variables that imply a conflicting relationship with the divine or spiritual or a doubt about one’s own beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…As an aside, inverse relationships have also been found between trust in God and spiritual struggles with God [ 32 ]. Be that as it may, spiritual struggles are associated with severe anxiety and depression [ 87 ], psychological distress [ 88 ] and less positive mental health [ 89 ], which could explain, in turn, the serious consequences of mistrust in God. Even in the specific case of cancer, the religious/spiritual struggle was associated with greater symptom burden and poorer quality of life [ 90 ], as well as greater depression [ 91 ].…”
Section: Discussionmentioning
confidence: 99%